1997
DOI: 10.1007/pl00008103
|View full text |Cite
|
Sign up to set email alerts
|

Circumnutations: results from recent experiments on Earth and in space

Abstract: Results of experiments on circumnutations from the last few decades are discussed, particularly in regard to the relationship between gravity and circumnutations. Pertinent and new results from experiments in microgravity as well as results from ground-based studies are summarized, and questions with relevance to space activities are posed. Theoretical approaches to describe aspects of circumnutation are also discussed. The review indicates some areas where further research efforts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 60 publications
0
80
0
Order By: Relevance
“…This ambiguity has encouraged further discussion and experimentation on the relationship between gravitropism and circumnutation. By extending the earlier models, Johnsson (1997) hypothesized that circumnutation is generated by both gravitropism-dependent and -independent oscillators. Johnsson et al .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This ambiguity has encouraged further discussion and experimentation on the relationship between gravitropism and circumnutation. By extending the earlier models, Johnsson (1997) hypothesized that circumnutation is generated by both gravitropism-dependent and -independent oscillators. Johnsson et al .…”
Section: Introductionmentioning
confidence: 94%
“…Circumnutation might be composed of gravity-dependent and -independent components (Johnsson 1997). If this were the case in rice coleoptiles, it would be expected that the gravity-independent circumnutation remains on clino- rotated coleoptiles.…”
Section: Why Does Circumnutation Stop On Clinostats?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the former, gravity plays no role in the generation of the circumnutation, and in the latter, gravitropic reactions play a central role. Circumnutation is observed under both microgravity and 1 G conditions, although the characteristics seem to change under microgravity conditions (Brown and Chapman, 1984;Volkmann et al, 1986;Johnsson, 1997;Antonsen et al, 1995;Stanković et al, 1998). Thus at least it seems reasonable to assume the existence of an internal oscillator mechanism that is affected by gravitational stimuli (Johnsson, 1997).…”
Section: Graviresponse In Plants: Automorphosis Autotropism and Automentioning
confidence: 99%
“…Circumnutation is observed under both microgravity and 1 G conditions, although the characteristics seem to change under microgravity conditions (Brown and Chapman, 1984;Volkmann et al, 1986;Johnsson, 1997;Antonsen et al, 1995;Stanković et al, 1998). Thus at least it seems reasonable to assume the existence of an internal oscillator mechanism that is affected by gravitational stimuli (Johnsson, 1997). Recently it has been reported that a gravitropic mutant of Japanese morning glory (Pharbitis nil or Ipomoea nil), Shidare-asagao (weeping), is also defective in circumnutation, and that both defect of circumnutation and abnormal gravitropism are attributable to a loss of PnSCR (SCARECROW) function, suggesting that shoot circumnutation requires gravisensing endodermal cells (Kitazawa et al, 2005).…”
Section: Graviresponse In Plants: Automorphosis Autotropism and Automentioning
confidence: 99%